An Analysis Students’ Writing Skills at Seventh Grade Of SMP Wahidiyah Kediri By Using Internet - Siti Nafi’yah; Avinta Ika Nurrahma (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Writing is one of important skill in English. Many students is difficult to write in English. This research focuses on students' abilities in write descriptive text by using internet.This research aims to know the students’ ability in writing’s skills at seventh grade A of SMP Wahidiyah Kediri by using internet in academic year 2022/2023. The method used in this research is descriptive quantitative research. The subject are 47 students. In collecting data, the researcher use tests writing as instrument. The components analyzed are developing ideas, organizing ideas, grammar and vocabulary. The Researcher analyze the writing ability of students by five categories: excellent, very good, good, enough, and poor. The results of this study that the students found difficulties in developing ideas on the text that they wrote. The organizing ideas found difficulty in writing how to deliver coherence sentences for descriptive text.The grammar component found difficulty in writing the correct sentence arrangement. The component vocabulary is also still found some difficulties in applying vocabulary English appropriately.